Pengaruh Kontaminan terhadap Sudut Kontak Hidropobik dan Karakteristik Arus Bocor pada Sampel Isolator Resin Epoksi Silane - Abdul Syakur; . Karnoto; Ratih Wahyu Wijayanti (Universitas Syiah Kuala, 2012)
Polymer insulators have become an alternative to change the ceramic insulator because it has a better dielectric properties, mass density is lighter and can be made at room temperature vulcanized so it is economically more advantageous. But, the disadvantage is prone to degradation due to environmental factors such as ultraviolet radiation, temperature, humidity or rain, and pollution, especially if located in the tropical areas. To overcome these disadvantages, silane materials was added to epoxy resin. This study uses an epoxy resin polymer material made of diglycidyl ether of bisphenol-A (DGEBA) and metaphenylene diamine (MPDA) and silane. Ratio of epoxy resin and silane were 60% and 40% respectively. Dimensions of the test material were 120 mm x 50 mm x 5 mm. The Inclined-Plane Tracking (IPT) method according to standard IEC 587:1984 was used. The NH4Cl and Gresik Industrial and Parangtritis beach contaminants were used in this research to compare it others. The results showed that the test sample with a contact angle 86.18Omore resistant to leakage current and insulation failure, it was indicated by the timing of the discharge in 17.001 s and insulation failure in 17.812 s. When a sample tests more hydrophobic then the leakage current and insulation failure longer to occurs. The degradation phenomenon is most severe damage from a beach Parangtritis contaminant than industrial and NH4Cl contaminants.